Immuno-informatics study identifies conserved T cell epitopes in non-structural proteins of Bluetongue virus serotypes: formulation of a computationally optimized next-generation broad-spectrum multi-epitope vaccine - Kolla, Harish Babu; Dutt, Mansi; Kumar, Anuj; Hebbandi Nanjunadappa, Roopa; Karakach, Tobias; Singh, Karam Pal; Kelvin, David; Clement Mertens, Peter Paul; Umeshappa, Channakeshava Sokke (Frontiers in Immunology, 2024)
Bluetongue (BT) poses a significant threat to the livestock industry, affecting various animal species and resulting in substantial economic losses. The existence of numerous BT virus (BTV) serotypes has hindered control efforts, highlighting the need for broad-spectrum vaccines. In this study, we evaluated the conserved amino acid sequences within key non-structural (NS) proteins of BTV (NS1, NS2, and NS3) and identified numerous highly conserved murine-and bovine-specific MHC class Irestricted (MHC-I) CD8+ and MHC-II-restricted CD4+ epitopes in the NS proteins. Subsequently, we screened these conserved epitopes based on antigenicity, allergenicity, toxicity, and solubility.We found many epitopes that meet these criteria within NS1 and NS2 proteins and developed in silico broad-spectrum vaccines. Utilizing automated Robetta and GalaxyWEB servers, we achieved structural modeling and refinement of the vaccine constructs. Protein-protein docking analysis demonstrated promising epitopes with strong binding affinities to Toll-like receptor 4. The stability of the docking complexes was assessed through extensive 100 nanoseconds molecular dynamics simulations, revealing stable complexes with minimal Root Mean Square Deviation and Root Mean Square Fluctuation values. Therefore, these next-generation vaccine designs are promising and warrant further investigation in wet lab experiments to assess their immunogenicity, safety, and efficacy for practical application in livestock. Our findings offer a robust framework for developing a comprehensive, broad-spectrum vaccine, potentially revolutionizing BT control and prevention strategies in the livestock industry.